Competencies for Youth and Sports officers in the Ministry of Youth and Sports Malaysia - Shariff, Zainah; Ismail, Maimunah (Kai Wang and P. Y. Gloria Wang, 2008)
The purpose of this study was to identify competencies required by Youth and Sports officers in Malaysia and to examine the relationship between competencies need with job tenure. This descriptive survey involved 94 officers in Grade S41 and S48, of the Ministry who were located at the federal and state levels. They were chosen as they were the key group of employees contributing most to the achievement of the ministry’s vision and objectives. The results show that the most required competencies were planning and computer application. The results also showed that there was no relationship between competencies need and job tenure. This result was due to the variability of educational and service backgrounds of the respondents. Recommendation for practice and further research are highlighted.